FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN LION GROUP PERWAKILAN KALIMANTAN - Dinan Dinan (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2018)
The research aims to examine and analyze the influence of leadership style, motivation and work discipline toward performance of employee in Lion Group Distric Kalimantan. Data collected through distribution of questionnaires and it is implemented to Lion Group Distric Kalimantan 112 employee. Analysis of data in this research using the help of SPSS version 27. A sampling technique uses a census method and data test technique is used within the research includes validity test by factor analysis, reliability test with cronbach. Classic  assumption test and double linear regression analysis, to verify and to prove the research hypothesis.Analysis result demonstrates that leadership style have a positive influence toward employee performance. Motivation have a positive influence toward employee performance  and   work  discipline  have  a  positive  influence  toward  employee performance.